Need satisfaction, motivation, and engagement among high-performance youth athletes: A multiple mediation analysis - Podlog, L.; Gustafsson, H.; Skoog, T.; Gao, Z.; Westin, M.; Werner, S.; Alricsson, M. (International Journal of Sport and Exercise Psychology, 2015)
The purpose of this investigation was to examine whether the various types of motivation articulated in self-determination theory (SDT) mediated the relationship between basic need satisfaction (i.e. competence, autonomy, and relatedness) and athlete engagement. Four types of motivation as assessed by the Situational Motivation Scale including intrinsic motivation, identified regulation, external regulation, and amotivation were examined as mediators of the need satisfaction-engagement relationship. Swedish downhill skiers (N = 192; n = 95 males, n = 97 females) aged 15-20 years completed questionnaires assessing the study variables of interest. Mediation analyses revealed that all four motivational regulations were significant partial mediators of the relationship between autonomy support and engagement. Moreover, except for external regulation, all three motivational regulations fully mediated the association between relatedness and engagement. Finally, intrinsic motivation and identified regulation partially mediated the relationship between competence and engagement. Findings support SDT contentions highlighting the importance of self-determined forms of motivation in mediating need satisfaction and engagement. The mediation patterns and directions for future research are discussed.